2014
DOI: 10.1111/jonm.12163
|View full text |Cite
|
Sign up to set email alerts
|

Work environment for Chinese nurses in different types of ICUs: a multisite cross-sectional survey

Abstract: Nurse administrators and health policy-makers should establish a healthy work environment for intensive care units nurses, especially for those from surgical intensive care units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 21 publications
1
14
3
1
Order By: Relevance
“…It appears that older nurses are more likely to be married, have had longer careers, and hold higher positions, and therefore, they are more likely to be better at carrying out their tasks. These findings that nurses’ demographic characteristics, such as work experience and educational level, affect their perceptions of the quality of care are supported by previous research (Bai et al., ). However, other studies have not found significant associations (Stalpers et al., ).…”
Section: Discussionsupporting
confidence: 84%
“…It appears that older nurses are more likely to be married, have had longer careers, and hold higher positions, and therefore, they are more likely to be better at carrying out their tasks. These findings that nurses’ demographic characteristics, such as work experience and educational level, affect their perceptions of the quality of care are supported by previous research (Bai et al., ). However, other studies have not found significant associations (Stalpers et al., ).…”
Section: Discussionsupporting
confidence: 84%
“…Bai et al . ). However, various authors mentioned that nurses attach much relevance to these factors.…”
Section: Discussionmentioning
confidence: 97%
“…Conversely, higher means for nurse‐perceived quality instead of overall job satisfaction were shown in two EoM II‐studies; in 34 US hospitals by Schmalenberg and Kramer () and in 28 Chinese ICUs (Bai et al . ). Cultural differences may have been influential; an explanation which may also be applicable for the low percentages of dissatisfied nurses in our study.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The EOMII scale can facilitate investigation of the extent to which the work environment supports or hinders nurses in providing high quality patient care. It has been widely used in the United States and countries outside the United States, such as Turkey (Yildirim, Kisa, & Hisar, ), The Netherlands (De Brouwer, Kaljouw, Kramer, Schmalenberg, & Achterberg, ) and China (Bai et al, ). For the first time, in our earlier study (Oshodi, Crockett, Bruneau, & West, ), the EOMII was used in England.…”
Section: Introductionmentioning
confidence: 99%